2021
DOI: 10.1038/s41598-021-83729-5
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of the incidence, various types and risk factors of malignancies in patients with dermatomyositis and polymyositis in Taiwan

Abstract: Our study aimed to investigate the incidence, risk factors and time to occurrence of malignancy in patients with dermatomyositis (DM) and polymyositis (PM). The electronic medical records of 1100 patients with DM and 1164 patients with PM were studied between January 2001 and May 2019. Malignancies after myositis were diagnosed in 61 (5.55%) patients with DM and 38 (3.26%) patients with PM. The cumulative incidence of malignancies in patients with DM were significantly higher than patients with PM (hazard rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
3
16
1
Order By: Relevance
“…The increased risk of cancer is associated with both dermatomyositis and other types of autoimmune myopathies. However, it is significantly higher in dermatomyositis with the incidence of malignancy ranging from 5.5 to 42% [ 20 , 21 ]. A recent meta-analysis of 5 studies involving 4538 patients showed that the risk of cancer increased 4.66-fold in patients with the disease compared to the general population [ 17 ].…”
Section: Dermatomyositis and Malignant Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…The increased risk of cancer is associated with both dermatomyositis and other types of autoimmune myopathies. However, it is significantly higher in dermatomyositis with the incidence of malignancy ranging from 5.5 to 42% [ 20 , 21 ]. A recent meta-analysis of 5 studies involving 4538 patients showed that the risk of cancer increased 4.66-fold in patients with the disease compared to the general population [ 17 ].…”
Section: Dermatomyositis and Malignant Diseasesmentioning
confidence: 99%
“…According to the analysis of 2 large cohorts of patients with dermatomyositis, the most frequently reported malignancies were breast cancer (24.5%), hematologic malignancies (17.0%), colorectal cancers (9.4%), and prostate cancer (9.4%) [ 23 ]. Studies conducted in the Asian population showed that the nasopharynx was the most common location of malignancy with the incidence of 22.5–62.5% of all cancers [ 24 , 25 ] (Table 1 ).…”
Section: Dermatomyositis and Malignant Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“… 79 , 80 For women, cancers with the greatest risk include breast, ovarian, and uterine cancer. 81 In a nationwide cohort study in Taiwan, cancers with the greatest risk associated with DM included nasopharyngeal carcinoma, followed by lung and breast cancers. 82 Universally accepted screening guidelines are lacking, but age appropriately cancer screening is recommended along with obtaining a complete blood count, liver function tests, urinalysis, fecal occult blood test and chest radiograph.…”
Section: Introductionmentioning
confidence: 99%
“…• Mechanic's hands 86 • Disease phenotypes vary by anti-ARS antibody, with those against non-Jo-1 ARS associated with earlier and more severe ILD and poor prognosis 87 • Association with anti-synthetase syndrome 67,81 Up to 20%…”
mentioning
confidence: 99%